(untitled) (Bhartiya Knowledge Systems, 2024)
This article presents the meaning of Dandaniti and Rajdharma. The researcher made an endeavor to understand the viewpoint of Manu regarding the meaning and various forms of punishment theory. Also, the researcher attempts to explain the various ways of punishment that are given to the offenders by the Hindu Shastra and by the contemporary criminal justice system.